America's Blessings : How Religion Benefits Everyone, Including Atheists. - Stark, Rodney (West Conshohocken : Templeton Press, 2012)
A few years ago, a debate between atheists and religious believers spilled out from the halls of academia and the pews of America's churches and into the public spotlight. A crop of atheist manifestos led the charge, surmounting and holding the tops of the nonfiction bestseller lists. This offensive brought on an outpouring of religious rebuttals. As both sides exchanged spirited volleys, accusations were leveled; myths, stereotypes, and strawmen arguments were perpetuated; and bitter hostility filled the air. Today many of these misconceptions and myths linger on, along with the generall.
Creating religious america -- Crime and prosocial behavior -- Fertility and family -- Sexuality -- Mental and physical health -- Generous citizenship -- Achievement and success -- Intellectual life -- Conclusion: counting our blessings.
Print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 050
Keywords: Christianity -- United States; Christianity -- Influence; Christianity and culture -- United States; Christianity -- Influence; Christianity -- United States; Christianity and culture -- United States; Religion; RELIGION -- History; TRAVEL -- Special Interest -- Religious; Christianity; Christianity and culture; Christianity -- Influence; United States; Electronic books